Zn-Based Deep Eutectic Solvent as the Stabilizing Electrolyte for Zn Metal Anode in Rechargeable Aqueous Batteries - Thorat, Gaurav M.; Ho, Van-Chuong; Mun, Junyoung (Frontiers in Chemistry, 2022)
Owing to its low cost and high safety, metallic zinc has received considerable attention as an anode material for zinc aqueous batteries (ZIBs). However, the Zn metal instability as a result ultrafast of obstinate dendrite formation, free-water-induced parasite reactions, and corrosive electrolytes has detrimental effects on the implementation of ZIBs. We present an alternative stable electrolyte for ZIBs based on a zinc chloride/ethylene glycol deep eutectic solvent (DES). This electrolyte consists of abundant low-cost materials and a utilizable Zn2+ concentration of approximately 1 M. It combines the advantages of the aqueous and DES media to provide safe and reversible Zn plating/stripping with a two-fold increase in the cycling life compared to that of conventional aqueous electrolytes. With these advantages, the Zn symmetric cell operates at 0.2 mA cm−2 for 300 h. Due to its high efficiency and compositional versatility, this electrolyte enables the investigation of a non-aqueous electrolyte family for ZIBs that fulfill grid-scale electrical energy storage requirements.